2019
DOI: 10.26434/chemrxiv.11410125.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing the Affinity of an O-Antigen Polysaccharide Binding Site in Shigella Flexneri Bacteriophage Sf6 Tailspike Protein

Abstract: We analysed the tailspike from bacteriophage Sf6 in complex with the O-polysaccharide of the pathogen Shigella flexneri. The conformational space populated by the polyrhamnose backbone of the S. flexneri O-polysaccharide as studied by an octasaccharide in complex with Sf6TSP could be well described with 2D 1H,1H-trNOESY NMR, utilizing a combination of methine-methine and methine-methyl correlations. The results are in good agreement with the conformations obtained from molecular dynamics (MD) simulations. To e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Previous work using molecular dynamics demonstrated that mutations near the O-antigen binding site of the Sf6 tailspike can dramatically affect the flexibility of the site (Kunstmann, et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work using molecular dynamics demonstrated that mutations near the O-antigen binding site of the Sf6 tailspike can dramatically affect the flexibility of the site (Kunstmann, et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These changes could allow for a better fit of the glucosylated 2a 2 O-antigen structure, which likely assumes a helical rather than a linear shape (West, et al 2005). Previous work using molecular dynamics demonstrated that mutations near the O-antigen binding site of the Sf6 tailspike can dramatically affect the flexibility of the site (Kunstmann, et al 2020). As part of their study, Kunstmann et al modeled a T443C substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental determination and verification of RBP function is still needed, and macromolecular (baseplate and tail) cryo-EM studies to decipher activation mechanisms of phage tails are highly desirable. Importantly, more and more RBP-ligand interactions are being systematically dissected on an atomic level to reveal residues and regions that are critical for ligand binding and which are amenable to mutation in order to manipulate RBP-binding affinities and modification of binding ranges [29][30][31]35,37,66,68,74,75]. Such studies are essential for further development of RBPs as bioprobes or depolymerase tools and provide the necessary atomic-resolution 'blueprints' for host range programming of whole, engineered phage therapeutics.…”
Section: Understanding Receptor-binding Proteinligand Interactions: W...mentioning
confidence: 99%